2014
DOI: 10.11138/mltj/2014.4.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the biological effects of extracorporeal shock wave therapy on tendon models. A review of the literature

Abstract: SummaryEncouraging results using extracorporeal shock wave therapy (ESWT) for treating chronic tendinopathies were recently obtained, although the specific mechanisms by which it induces therapeutic effects remain largely unknown. In order to provide possible explications of such clinical efficacy, several reports have investigated the effects of ESWT on animal models and different kind of cultured cells. Our contribute in establishing the potential outcome of ESWT on human primary cultured tenocytes, derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
0
44
0
7
Order By: Relevance
“…Evidence from a recent study of human tendons suggested that the mechanical stimulus of ESWT aids tendon remodeling by promoting inflammatory and catabolic processes that are associated with the removal of damaged matrix constituents 42. In vitro studies have further suggested that ESWT increases tendon healing through the stimulation of cell proliferation and motility, neovascularization, and expression of critical differentiation genes 43. However, these in vitro findings cannot be automatically generalized to the in vivo conditions in human tendinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a recent study of human tendons suggested that the mechanical stimulus of ESWT aids tendon remodeling by promoting inflammatory and catabolic processes that are associated with the removal of damaged matrix constituents 42. In vitro studies have further suggested that ESWT increases tendon healing through the stimulation of cell proliferation and motility, neovascularization, and expression of critical differentiation genes 43. However, these in vitro findings cannot be automatically generalized to the in vivo conditions in human tendinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Both are regenerative treatments but their mechanism of action in vivo is still unclear. The rational of applying in vivo ESWT on tendons is supported by the results obtained with shockwaves on models in vitro, such as enhancing cell proliferation, migration and secretory activity of human primary cultured tenocytes 44 . Basic science studies about PRP mechanism action show that growth factors in PRP significantly enhance the healing of tendon injuries such as tendinopathy 45 .…”
Section: Conservative Treatment For Insertional Achilles Tendinopathymentioning
confidence: 76%
“…Experimental animal studies demonstrated a significant increase in the ingrowth of neovascularization associated with increased expressions of angiogenic growth indicators in tendon, bone, and tendon-bone interface, which might play a role in the improvement of blood supply and healing, which in turn can improve subchondral bone remodeling and prevent femoral head collapse [21–23]. A close relationship between the decrease of substance P release and consecutive pain reduction after shock wave treatment has also been reported [2426].…”
Section: Discussionmentioning
confidence: 99%